Outreach focused CanSat project - Chan, Ming Hui (2019)
The CanSat Workshops are developed to introduce general satellite development concept and processes to students in local Pre-University institutions and below. The CanSat is a platform representing a scaled-down version of a conventional Low Earth Orbit satellite, based within a small Aluminium can commonly use in canned drinks or canned foodstuff. The CanSat is not designed to obit at high altitudes, instead, it is meant to simulate simple functions of a conventional satellite and is usually deployed via a sounding rocket or free fall from an altitude required by the mission. The onboard sensor payload will be activated to record any relevant data and transmit the information back to the Ground Station as the descent progresses. This project encompasses 2 CanSat concepts with differing payloads and development difficulty to cater for different educational scope. In addition, a data acquisition platform based on Microsoft Excel using an add-on programmed with Excel VBA language has been adopted for both CanSats to facilitate ease of data collection and visualisation for users of the CanSats.